A degradable three-phase polymer mixed membrane with core-shell structure and its preparation method and application
By introducing PGA and PBS into PLA, and using core-shell structure design, combined with epoxy soybean oil branched cardis phenol ether as a compatibilizer, the problem of insufficient gas barrier and flexibility in food packaging is solved, and the material performance is significantly improved and the effective application of food preservation is achieved.
Patent Information
- Application Number
- CN202411143133.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-08-20
AI Technical Summary
The application of existing polylactic acid (PLA) in the food packaging field is limited by its brittleness and poor gas barrier properties.
By introducing the compatibilizer epoxy soybean oil branched cardis phenol ether, combined with the core-shell structure design, the PGA/PBS core-shell structure formed is dispersed in the PLA matrix with a highly barrier but easily hydrolyzed polyglycolic acid (PGA) as the core and flexible polybutylene succinate (PBS) as the shell.
It significantly improves the flexibility and gas barrier properties of PLA, improves the mechanical properties of the material, and has the ability to resist ultraviolet radiation, and is suitable for food preservation packaging.
Smart Images

Figure CN118931133B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a degradable three-phase polymer mixed membrane with a core-shell structure and a preparation method and application thereof. Background Art
[0002] Polylactic acid (PLA) is known for its outstanding high strength, high modulus, excellent transparency and biocompatibility. However, its brittleness and poor gas barrier properties limit the application potential of PLA in food packaging. In order to overcome these limitations and broaden the application scope of PLA, researchers have previously studied the strategy of binary blending of PLA with a variety of biodegradable polymers. These polymers include polybutylene succinate (PBS), polyglycolic acid (PGA) and polybutylene adipate / terephthalate (PBAT). Through blending, the aim is to improve the flexibility and gas barrier properties of PLA, thereby optimizing its performance as a food packaging material.
[0003] The core-shell structure achieves structural assembly at the material level by utilizing the complementary properties of different polymers, and has become an effective means in polymer modification research. The advantages of the core-shell structure include improving the stability and reactivity of the material, and customizing the properties of the material according to the composition and thickness of the shell. Due to the significant differences in properties between polymers, such as the melting temperatures of PBS and PGA differ by about 100°C, this poses a compatibility challenge to their blending. During the melt blending process, phase separation of different polymers may lead to reduced performance. Summary of the invention
[0004] In order to solve the problems existing in the above-mentioned prior art, the present invention introduces a compatibilizer into the polymer blend system, and by enhancing the interaction between polymers, reduces the size of the dispersed phase, thereby improving the overall performance of the blend. The present invention provides a degradable three-phase polymer mixed film with a core-shell structure, and a preparation method and application thereof, and provides an improved PLA-based mixed material. Through the "core-shell" structural design strategy, PGA with high barrier properties but prone to hydrolysis is used as the core, and PBS with good flexibility is used as the shell, and the formed PGA / PBS core-shell structure is dispersed in the PLA matrix. By introducing PBS and PGA into PLA, not only the flexibility and gas barrier properties are improved, but also through the innovative application of the core-shell structure, a significant improvement in material performance is achieved.
[0005] One of the technical solutions provided by the present invention:
[0006] A degradable three-phase polymer mixed membrane with a core-shell structure, wherein the raw materials include PLA (polylactic acid), PGA (polyglycolic acid), PBS (polybutylene succinate) and an epoxy compatibilizer, wherein the mass ratio of the PLA, PGA and PBS is (5-8):1:(1-4); the core-shell structure is a PGA / PBS core-shell structure with PGA as the core and PBS as the shell dispersed in a PLA matrix.
[0007] Preferably, the mass ratio of PLA, PGA and PBS is (5-6):1:(3-4).
[0008] Preferably, the mass ratio of PLA, PGA and PBS is 6:1:3.
[0009] Preferably, the epoxy compatibilizer is selected from epoxidized soybean oil branched cardanol ether or Joncryl ADR 4468, more preferably epoxidized soybean oil branched cardanol ether.
[0010] The present invention enhances the bonding force of the phase interface and improves the mechanical properties of the mixed film by adding an epoxy compatibilizer.
[0011] The preparation method of the epoxy soybean oil branched cardanol ether is as follows: ESO (epoxidized soybean oil) and CD (cardanol) are mixed and then subjected to a catalytic reaction; the product obtained by the catalytic reaction is mixed with concentrated sulfuric acid and heated; a mixture of glacial acetic acid and hydrogen peroxide is added dropwise to carry out a stirring reaction; after the reaction is completed, extraction and separation are carried out, and the solvent is removed to obtain the epoxy soybean oil branched cardanol ether.
[0012] Preferably, the molar ratio of ESO to CD is 3:1, the catalyst in the catalytic reaction is hydrochloric acid, the catalytic reaction temperature is 200°C, the reaction time is 30 min, the ratio of the added amount of the product obtained by the catalytic reaction, concentrated sulfuric acid, glacial acetic acid and hydrogen peroxide is 100 g: 2 mL: 10 mL: 20 mL, the mass concentration of the concentrated sulfuric acid is 98%, the concentration of the glacial acetic acid is 3 equivalents, and the mass concentration of the hydrogen peroxide is 30%. The heating temperature is 65°C, and the stirring reaction time is 4 hours.
[0013] The second technical solution provided by the present invention is:
[0014] A method for preparing the above-mentioned degradable three-phase polymer mixed membrane with a core-shell structure comprises the following steps:
[0015] S1. PGA, PBS and epoxy compatibilizer are mixed, melt extruded and granulated to obtain a binary mixed material masterbatch;
[0016] S2. PLA, epoxy compatibilizer and the binary mixed material masterbatch are mixed, and melt extruded and granulated to obtain a ternary mixed material masterbatch;
[0017] S3. Casting the ternary mixed material masterbatch to obtain a degradable three-phase polymer mixed film.
[0018] Preferably, the epoxy compatibilizer added in S1 is 0.5 phr of the total mass of PGA and PBS.
[0019] Preferably, the epoxy compatibilizer added in S2 is 0.5 phr of the total mass of PLA and the binary mixed material masterbatch.
[0020] Preferably, the temperature of the melt extrusion granulation in S1 and S2 is 195-225°C.
[0021] Preferably, the temperature of the tape casting in S3 is 180-230°C.
[0022] The third technical solution provided by the present invention is:
[0023] An application of the above-mentioned degradable three-phase polymer mixed film with a core-shell structure in food preservation.
[0024] Preferably, the food is broccoli.
[0025] Compared with the prior art, the present invention has the following advantages and technical effects:
[0026] The degradable three-phase polymer mixed film with a core-shell structure provided by the present invention has high gas barrier and ultraviolet shielding properties. The "core-shell" structure can realize orderly assembly at the material level and enhance the polymer mixed system by utilizing complementary properties. The present invention enhances the flexibility and barrier properties of polylactic acid (PLA) by mixing polyglycolic acid (PGA) to improve gas barrier properties and mixing with polybutylene succinate (PBS) to improve flexibility. Using PBS as a shell structure to wrap the PGA core solves the problem of rapid hydrolysis of PGA. The interfacial bonding force is enhanced by adding an epoxy soybean oil cardanol ether bio-based compatibilizer, thereby improving the mechanical properties of the ternary mixed film. Among them, the 6L1G3B / E film effectively prevents oxygen from contacting food, thereby maintaining its freshness and quality. In addition, another key advantage of the 6L1G3B / E film is its ability to resist ultraviolet radiation. Exposure to ultraviolet radiation can accelerate the degradation of certain elements in food, affecting its taste and nutritional value. Therefore, the anti-ultraviolet properties of this membrane material can effectively protect food from harmful ultraviolet rays. In addition, the biodegradability of 6L1G3B / E film provides a sustainable solution for environmental protection and can be used as an effective packaging film due to its excellent mechanical properties, oxygen barrier properties, UV resistance and biodegradability.
[0027] The present invention discloses a "core-shell" structure design strategy, using PGA with high barrier properties but prone to hydrolysis as a core and PBS with good flexibility as a shell, and the formed PGA / PBS core-shell structure is dispersed in a PLA matrix. By introducing PBS and PGA into PLA, not only the flexibility and gas barrier properties are improved, but also the innovative application of the core-shell structure has achieved a significant improvement in material performance. In addition, the bio-based compatibilizer used in the present invention is an epoxy soybean oil branched cardanol ether prepared by Chinese patent CN202310666308.9, which has an excellent volume expansion effect, not only solves the problem of poor compatibility of biodegradable polyester two-phase, but also can enhance the interfacial bonding force of PBS / PGA two-phase, thereby improving the mechanical properties of PLA / PGA / PBS three-phase mixed film. In addition, it can replace petroleum-based compatibilizers to achieve full degradation. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0029] Figure 1 The transverse and longitudinal scanning electron microscope images of the three-phase polymer mixed membranes prepared in Comparative Examples 5 and 6;
[0030] Figure 2 The transverse and longitudinal scanning electron microscope images of the three-phase polymer mixed membranes prepared in Comparative Examples 7 and 8;
[0031] Figure 3 The transverse and longitudinal scanning electron microscope images of the three-phase polymer mixed membranes prepared in Examples 11 and 15;
[0032] Figure 4 The figures are the tensile performance diagrams of the ternary mixed material strips of Comparative Examples 1-4 and Examples 2-9, the left figure is a bar graph of tensile strength determination, and the right figure is a bar graph of elongation at break determination;
[0033] Figure 5 5(a) and 9(b) are comparison diagrams of soil hydrolysis experiments of three-phase polymer mixed membranes prepared in Comparative Example 5(a) and Comparative Example 9(b);
[0034] Figure 6 The ultraviolet transmittance graph of the three-phase polymer mixed films prepared in Comparative Examples 5-8 and Examples 11 and 15;
[0035] Figure 7 The front view (above) and top view (below) of different packaging bags keeping broccoli fresh at different time periods;
[0036] Figure 8 The left figure in the middle is a graph showing the weight loss rate changes during storage of the three-phase polymer mixed membranes prepared in Examples 11, 15 and Comparative Example 6, as well as pure PLA, PE and broccoli exposed to air; the right figure is a partial enlarged graph of the weight loss rate change graph;
[0037] Fig. 9 The graph of the changes in oxygen and carbon dioxide content in the packaging bag during storage of the three-phase polymer mixed films prepared in Examples 11, 15 and Comparative Example 6, as well as broccoli made of pure PLA, PE and exposed to air. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The sources of the raw materials used in the embodiments of the present invention are as follows:
[0044] Cardanol (CD): Huakai Resin Biochemical Co., Ltd., Jining, Shandong, China;
[0045] Epoxidized soybean oil (ESO): Macklin Co., Ltd., Shanghai, China;
[0046] ADR 4468: BASF SE;
[0047] Polylactic acid (PLA): Nature Works, USA, brand number 4032D;
[0048] Polyglycolic acid (PGA): Shanghai Pujing Chemical Technology Co., Ltd.
[0049] Polybutylene succinate (PBS): produced by Showa Corporation of Japan, with the brand name 1001MD.
[0050] Example 1 Preparation method of epoxidized soybean oil branched cardanol ether
[0051] (1) ESO and CD were mixed in a molar ratio of 3:1 and placed in a three-necked flask equipped with a magnetic stirrer. A drop of hydrochloric acid was added as a catalyst, and then reacted at a constant temperature of 200°C for 30 minutes to obtain a product.
[0052] (2) 100 g of the product obtained in step (1) was mixed with 2 mL of H2SO4 (98 wt.%) and heated to 65°C, and then a mixture of 10 mL of glacial acetic acid (3 equivalents) and 20 mL of H2O2 (30 wt.%) was added dropwise, and the mixed solution was magnetically stirred at 65°C for 4 h. After the reaction was completed, the product in the organic phase was extracted and separated in dichloromethane, and then the organic phase was removed by rotary evaporation to obtain epoxy soybean oil branched cardanol ether, which was recorded as ESO3-ECD.
[0053] The yield of the obtained bio-based epoxy compatibilizer ESO3-ECD is 90%, and the epoxy value is 6.62%.
[0054] In order to test the mechanical properties of the PLA / PGA / PBS mixed material, the present invention prepared PLA / PGA / PBS ternary mixed material strips through Examples 2-9 and Comparative Examples 1-4.
[0055] Example 2
[0056] (1) PGA, PBS and ESO3-ECD obtained in Example 1 are mixed and granulated by twin-screw melt extrusion to obtain a binary mixed material masterbatch, and the temperature of the extruder from the feeding zone to the head zone is 195-225°C (the temperatures of the six heating zones from the feeding zone to the head are set to: 195 / 200 / 205 / 210 / 220 / 225°C, respectively); wherein the mass ratio of PGA to PBS is 1:4, and the amount of the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 added is 0.5phr of the total mass of PGA and PBS.
[0057] (2) PLA, the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 and the binary mixed material masterbatch obtained in step (1) are mixed and then melt-extruded using a twin-screw extruder to obtain a ternary mixed material masterbatch. The temperature of the extruder from the feeding zone to the die zone is 195-225°C (the temperatures of the six heating zones from the feeding zone to the die are set to: 195 / 200 / 205 / 210 / 220 / 225°C, respectively); wherein PLA and the binary mixed material masterbatch obtained in step (1) are mixed in a mass ratio of 1:1, and the amount of the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is 0.5phr of the total mass of PLA and the binary mixed material masterbatch. The mass ratios of PLA, PGA and PBS in the ternary mixed material masterbatch are 5:1:4, respectively, and the content of ESO3-ECD is 1phr.
[0058] (3) Then, the obtained ternary mixed material masterbatch was injection molded at 200° C. using an injection molding machine to obtain PLA / PGA / PBS ternary mixed material specimens.
[0059] Example 3
[0060] The same as Example 2, except that the mass ratios of PLA, PGA and PBS are 6:1:3 respectively.
[0061] Example 4
[0062] The same as Example 2, except that the mass ratios of PLA, PGA and PBS are 7:1:2 respectively.
[0063] Example 5
[0064] The same as Example 2, except that the mass ratio of PLA, PGA and PBS is 8:1:1 respectively.
[0065] Example 6
[0066] (1) PGA, PBS and ADR 4468 were mixed and granulated by twin-screw melt extrusion to obtain a binary mixed material masterbatch, and the temperature of the extruder from the feeding zone to the head zone was 195-225° C. (the temperatures of the six heating zones from the feeding zone to the head were set to: 195 / 200 / 205 / 210 / 220 / 225° C. respectively); wherein the mass ratio of PGA to PBS was 1:4, and the amount of ADR 4468 added was 0.5 phr of the total mass of PGA and PBS.
[0067] (2) PLA, ADR 4468 and the binary mixed material masterbatch obtained in step (1) are mixed and then melt-extruded by a twin-screw extruder to obtain a ternary mixed material masterbatch, the temperature of the extruder from the feeding zone to the die zone is 195-225°C (the temperatures of the six heating zones from the feeding zone to the die are set to: 195 / 200 / 205 / 210 / 220 / 225°C respectively); wherein PLA and the binary mixed material masterbatch obtained in step (1) are mixed in a mass ratio of 1:1, and the amount of ADR 4468 added is 0.5phr of the total mass of PLA and the binary mixed material masterbatch. The mass ratios of PLA, PGA and PBS in the ternary mixed material masterbatch are 5:1:4 respectively, and the content of ADR 4468 is 1phr.
[0068] (3) Then, the obtained ternary mixed material masterbatch was injection molded at 200° C. using an injection molding machine to obtain PLA / PGA / PBS ternary mixed material specimens.
[0069] Example 7
[0070] Same as Example 6, except that the mass ratios of PLA, PGA and PBS are 6:1:3 respectively.
[0071] Example 8
[0072] Same as Example 6, except that the mass ratios of PLA, PGA and PBS are 7:1:2 respectively.
[0073] Example 9
[0074] Same as Example 6, except that the mass ratio of PLA, PGA and PBS is 8:1:1 respectively.
[0075] Comparative Example 1
[0076] The same as Example 2, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0077] Comparative Example 2
[0078] The same as Example 3, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0079] Comparative Example 3
[0080] The same as Example 4, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0081] Comparative Example 4
[0082] The same as Example 5, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0083] Example 10
[0084] Steps (1) and (2) are the same as in Example 2;
[0085] (3) Using a tape casting machine at 180-230° C. (the temperature settings of the four zones from the feeding zone to the machine head are: 180 / 200 / 215 / 230° C.), the obtained mixed material masterbatch is tape cast to obtain a PLA / PGA / PBS three-phase polymer mixed film.
[0086] Embodiment 11
[0087] Same as Example 10, except that the mass ratios of PLA, PGA and PBS are 6:1:3 respectively.
[0088] Example 12
[0089] Same as Example 10, except that the mass ratios of PLA, PGA and PBS are 7:1:2 respectively.
[0090] Embodiment 13
[0091] Same as Example 10, except that the mass ratio of PLA, PGA and PBS is 8:1:1 respectively.
[0092] Embodiment 14
[0093] (1) PGA, PBS and ADR 4468 were mixed and granulated by twin-screw melt extrusion to obtain a binary mixed material masterbatch, and the temperature of the extruder from the feeding zone to the head zone was 195-225° C. (the temperatures of the six heating zones from the feeding zone to the head were set to: 195 / 200 / 205 / 210 / 220 / 225° C. respectively); wherein the mass ratio of PGA to PBS was 1:4, and the amount of ADR 4468 added was 0.5 phr of the total mass of PGA and PBS.
[0094] (2) PLA, ADR 4468 and the binary mixed material masterbatch obtained in step (1) are mixed and then melt-extruded by a twin-screw extruder to obtain a ternary mixed material masterbatch, the temperature of the extruder from the feeding zone to the die zone is 195-225°C (the temperatures of the six heating zones from the feeding zone to the die are set to: 195 / 200 / 205 / 210 / 220 / 225°C respectively); wherein PLA and the binary mixed material masterbatch obtained in step (1) are mixed in a mass ratio of 1:1, and the amount of ADR 4468 added is 0.5phr of the total mass of PLA and the binary mixed material masterbatch. The mass ratios of PLA, PGA and PBS in the ternary mixed material masterbatch are 5:1:4 respectively, and the content of ADR 4468 is 1phr.
[0095] (3) Using a tape casting machine at 180-230°C (the temperature settings of the four zones from the feeding zone to the machine head are: 180 / 200 / 215 / 230°C), the obtained ternary mixed material masterbatch is tape cast to obtain a PLA / PGA / PBS three-phase polymer mixed film.
[0096] Embodiment 15
[0097] Same as Example 14, except that the mass ratios of PLA, PGA and PBS are 6:1:3 respectively.
[0098] Example 16
[0099] Same as Example 14, except that the mass ratios of PLA, PGA and PBS are 7:1:2 respectively.
[0100] Embodiment 17
[0101] Same as Example 14, except that the mass ratio of PLA, PGA and PBS is 8:1:1 respectively.
[0102] Comparative Example 5
[0103] The same as Example 10, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0104] Comparative Example 6
[0105] The same as Example 11, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0106] Comparative Example 7
[0107] The same as Example 12, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0108] Comparative Example 8
[0109] The same as Example 13, except that the bio-based epoxy compatibilizer ESO3-ECD obtained in Example 1 is not added in step (1).
[0110] Comparative Example 9
[0111] The same as comparative example 8, except that the mass ratios of PLA, PGA and PBS are 4:1:5 respectively.
[0112] Table 1 Summary of raw material composition of ternary mixed material strips
[0113]
[0114] Note: 6L1G3B represents the ratio of PLA / PGA / PBS is 6:1:3, and the same applies to the others; A represents the added compatibilizer is ADR4468; E represents the added compatibilizer is ESO3-ECD.
[0115] Table 2 Summary of three-phase polymer mixed membrane formulations
[0116]
[0117] Technical Effects
[0118] 1. The products obtained in each embodiment and comparative example were characterized by the following method:
[0119] (1) The mechanical properties of ternary mixed material strips and three-phase polymer mixed films were tested using GB / T1040.1-2006 on an electronic universal testing machine controlled by a microcomputer (CMT6104, China) to obtain the elongation at break (EB, %) and tensile strength (TS, MPa) of the samples. The clamp spacing was set to 50 mm, the tensile speed was 50 mm / min, and each group of samples was tested 5-10 times. The average value was taken and the error was calculated.
[0120] (2) The microstructure of the samples was analyzed by scanning electron microscopy (SEM) under the condition of JSM-6700F voltage of 10 kV. Each group of samples was immersed in liquid nitrogen for 15 min, and a thin layer of gold was coated on the fracture surface to improve the conductivity of the samples.
[0121] (3) The three-phase polymer blend membrane was cut into 5 cm × 10 cm samples for evaluation in a real soil environment. A soil burial experiment was conducted in western Beijing. Various samples were buried in the soil to a depth of 20 cm. Subsequently, the buried samples were watered regularly to simulate the soil in the natural environment. Every month, one sample was selected from each batch for testing.
[0122] (4) The O2 permeability of the three-phase polymer blend membrane was measured using a VAC-V2 differential pressure gas permeometer at 23°C and 30% relative humidity according to ASTM D3985.
[0123] (5) The transmittance of the three-phase polymer blend film in the range of 200 to 800 nm was measured using an ultraviolet-visible spectrophotometer (UV-3600, Shimadzu Corporation, Japan).
[0124] (6) The oxygen and carbon dioxide contents in different packaging films were measured using a handheld oxygen / carbon dioxide analyzer (Oxybaby M+i O2 / CO2, Witte, Germany), and the oxygen and carbon dioxide contents were expressed as percentage (%).
[0125] 2. Characterization results and analysis are as follows:
[0126] Figure 1 The transverse and longitudinal scanning electron microscope images of the three-phase polymer mixed membranes prepared in Comparative Examples 5 and 6;
[0127] Figure 2 The transverse and longitudinal scanning electron microscope images of the three-phase polymer mixed membranes prepared in Comparative Examples 7 and 8;
[0128] pass Figure 1-2 The transverse and longitudinal morphologies of the three-phase polymer mixed film were analyzed. It was found that when the ratio of PLA / PGA / PBS was 5:1:4 and 6:1:3, the three-phase mixed material could form a structure with PLA as the matrix, PGA as the core, and PBS as the shell. As the PBS content decreased, it became difficult for it to form a core-shell structure with PGA. However, when the ratio of PLA / PGA / PBS was 7:1:2 and 8:1:1, PBS and PGA were basically dispersed in the PLA matrix in the form of separate particles.
[0129] The present invention also evaluates the effects of two compatibilizers (ADR 4468 and the bio-based epoxy compatibilizer ESO3-ECD prepared in Example 1) in four formulations (5:1:4, 6:1:3, 7:1:2 and 8:1:1). The mechanical properties of the injection molded specimens of the mixed materials obtained in Examples 2-9 and Comparative Examples 1-4 were tested, and their tensile properties are shown in Tables 3 and Figure 4 The tensile properties of the ternary mixed materials of Comparative Examples 1-4 and Examples 2-9 are shown in the graphs, and the compatibilization effect of different compatibilizers is studied. Figure 4 It can be seen that the addition of ADR or ESO3-ECD can improve the tensile strength and elongation at break of the mixed materials compared with the uncompatibilized blends, proving that the addition of compatibilizers has the effect of enhancing the interfacial bonding force. The epoxy groups in the compatibilizers can react with the carboxyl and / or hydroxyl groups of PBS and PGA, thereby promoting effective fixation between the phases.
[0130] By analyzing Table 3 and Figure 4 It was found that ESO3-ECD more effectively promotes compatibility in blends with low PLA content, resulting in better mechanical properties of the blends; while ADR shows better compatibilization effect in systems with high PLA content. Due to its specific chemical structure, ESO3-ECD is more inclined to form a bridging effect between PBS and PGA phases, which is particularly evident in blends with low PLA content. This bridging effect not only enhances the compatibility of PBS and PGA phases, but also improves the elongation at break and overall toughness of the material. As a multifunctional compatibilizer, ADR can form multiple cross-linking points with the molecular chains of PLA, PBS and PGA, thereby achieving more effective molecular chain entanglement and interfacial bonding in systems with high PLA content. This enhanced interfacial bonding force helps to disperse stress and improve the toughness and tensile strength of the material. It can be seen from the mechanical property measurement results in Table 3 that when the mass ratio of PLA, PGA and PBS changes without adding a compatibilizer, the mechanical properties will also be affected (such as Comparative Example 1 and Example 6). As the amount of PLA added increases, the mechanical properties are significantly improved.
[0131] Table 3 Tensile properties of ternary mixed material strips
[0132] sample name Tensile strength(MPa) Elongation at break (%) Comparative Example 1 5L1G4B 41.3±0.8 5.2±0.8 Comparative Example 2 6L1G3B 36.1±0.8 4.0±0.0 Comparative Example 3 7L1G2B 46.3±1.3 11.5±1.4 Comparative Example 4 8L1G1B 42.3±0.5 7.2±0.4 Example 2 5L1G4B / E 43.7±2.3 5.8±0.5 Example 3 6L1G3B / E 46.9±1.4 20±2.6 Example 4 7L1G2B / E 47.3±0.1 11.7±1.3 Example 5 8L1G1B / E 46.5±0.8 7.9±0.5 Example 6 5L1G4B / A 38.7±1.4 4.9±0.5 Example 7 6L1G3B / A 42.5±1.4 5.3±0.3 Example 8 7L1G2B / A 54.2±1.6 13.9±2.1 Example 9 8L1G1B / A 55.0±0.4 7.8±0.3
[0133] Based on the above analysis, it is found that the PLA / PGA / PBS ratio of 6:1:3 has a better core-shell structure, and the toughness (elongation at break) of the mixed material is optimal after adding ESO3-ECD. Therefore, the present invention mainly conducts mechanical analysis on the cast film of the 6L1G3B component, as shown in Table 4. Similarly, the component with ESO3-ECD added has the best performance, that is, the mechanical properties of 6L1G3B / E in both the longitudinal and transverse directions are optimal.
[0134] Figure 3 The horizontal and vertical scanning electron microscope images of the three-phase polymer mixed membranes prepared in Examples 11 and 15 are shown; by comparison, it is found that the 6L1G3B without and with compatibilizers has a structure in which PLA is a continuous matrix material, PBS is a shell, and PGA is a core. In the three-phase mixed membrane obtained in Comparative Example 6 without volume-enhanced modification, due to the weak bonding force between the phase interfaces, the rigid PGA particles will be pulled out of the flexible PBS matrix during the brittle fracture of the sample, leaving holes in the cross section of the three-phase polymer mixed membrane obtained in Comparative Example 6. In Example 11, after 1phr of ESO3-ECD was added, the two-phase interface in the three-phase mixed membrane was significantly reduced, and the horizontal and vertical sections became smooth, which further illustrates the good volume-enhancing effect of ESO3-ECD.
[0135] Table 4 Tensile properties of three-phase polymer mixed films
[0136]
[0137] Biodegradable polyesters such as PLA, PBS and PGA usually begin to degrade in natural environments, such as soil, through hydrolysis reactions. The hydrolytic cleavage of ester bonds leads to the degradation of the macromolecular structure, which represents a key initial stage in the degradation process of polyesters. Subsequently, the metabolic activity of microorganisms can further accelerate this process. PGA is more likely to undergo rapid hydrolysis due to the strong hydrogen bonds in its molecular structure, in contrast to other polyesters. There are physical interactions between PGA molecules through weak intermolecular hydrogen bonds between the hydrogen atoms of the CH2 connection and the oxygen atoms of the COC ether connection.
[0138] The hydrolysis rate of the three polyesters was in the order of PGA>PBS>PLA, with PLA having a slower hydrolysis rate than PBS. After observing the SEM of samples at different soil burial experiment time points, it was clear that PGA underwent significant hydrolysis in the early stages, such as Figure 5 The soil hydrolysis test comparison of the three-phase polymer mixed membranes prepared in Comparative Examples 5 and 9 is shown in the figure: after 60 days of soil burial, visible pore structure was observed on the surface of sample 4L1G5B, and surface damage became obvious on the 120th day. This phenomenon is mainly controlled by the hydrolysis behavior of PGA. In contrast, the surface profile of 5L1G4B remained mainly consistent during the first 90 days, which is attributed to its unique "core-shell" structure, in which PBS encapsulates PGA in the PLA matrix to form a protection against hydrolysis.
[0139] As can be seen from Table 5, compared with the mixed film of Comparative Example 6 without adding a compatibilizer and the mixed film of Example 15 with adding an ADR 4468 compatibilizer, the mixed film prepared in Example 11 exhibits the lowest oxygen permeability coefficient and has good barrier properties.
[0140] Table 5 Gas permeability of three-phase polymer mixed membranes
[0141]
[0142]
[0143] Figure 6The UV transmittance graph of the three-phase polymer mixed film prepared in Comparative Examples 5-8 and Examples 11 and 15. The UV spectrum is divided into three parts: UVC (200-280nm), UVB (280-320nm) and UVA (320-400nm). In the UVC (200-280nm) region, 6L1G3B / E exhibits a full shielding effect. In the UVB (280-320nm) region, the transmittance of 6L1G3B / E is less than 1%. In the UVA (320-400nm) region, the transmittance of 6L1G3B / E is less than 3%.
[0144] The three-phase polymer mixed films prepared in Example 11, Example 15 and Comparative Example 6 were used as packaging bags for broccoli preservation, and compared with pure PE film and pure PLA film, with air exposure as blank (CK), and were respectively used for broccoli preservation. Figure 7 The front view (above) and top view (below) of different packaging bags keeping broccoli fresh at different time periods; Figure 7 It can be seen that Examples 11 and 15 as well as Comparative Example 6 can all maintain the freshness of broccoli within a certain range.
[0145] Figure 8 The left figure in the middle is a graph showing the weight loss rate changes during storage of the three-phase polymer mixed membranes prepared in Examples 11, 15 and Comparative Example 6, as well as pure PLA, PE and broccoli exposed to air; the right figure is a partial enlarged graph of the weight loss rate change graph; Figure 8 It can be found that the three three-phase mixed membranes (6L1G3B, 6L1G3B / A and 6L1G3B / E) without and with compatibilizer all have good quality retention.
[0146] Fig. 9 The three-phase polymer mixed film prepared in Example 11, 15 and Comparative Example 6, as well as the changes in oxygen and carbon dioxide content in the packaging bag during storage of broccoli in pure PLA, PE and exposed to air. The experiment found that when the gas composition in the packaging bag reached a relative balance, the O2 content in the 6L1G3B, 6L1G3B / A and 6L1G3B / E packaging bags was equivalent to that of the PE film, at 0-3%, while the CO2 content was higher than that of the PE film, forming a low O2, high CO2 gas atmosphere. Compared with 6L1G3B / A and 6L1G3B / E, the oxygen content in the 6L1G3B / E packaging bag was lower, while the CO2 content was higher. The low O2, high CO2 atmosphere can effectively inhibit the respiration of broccoli, reduce the consumption of nutrients such as organic matter, and thus delay the aging of broccoli.
[0147] Oxygen is the main factor in food spoilage. Therefore, 6L1G3B / E film effectively prevents oxygen from contacting food, thereby maintaining its freshness and quality. In addition, another key advantage of 6L1G3B / E film is its ability to resist UV radiation. Exposure to UV radiation can accelerate the degradation of certain elements in food, affecting its taste and nutritional value. Therefore, the UV resistance of this film material can effectively protect food from harmful UV rays. In addition, the biodegradability of 6L1G3B / E film provides a sustainable solution for environmental protection. Due to its excellent mechanical properties, oxygen barrier properties, UV resistance and biodegradability, it can be used as an effective packaging film.
[0148] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. Application of a degradable three-phase polymer mixed film with a core-shell structure in food preservation, The raw materials of the degradable three-phase polymer mixed membrane with a core-shell structure include PLA, PGA, PBS and epoxy compatibilizer, and the mass ratio of PLA, PGA and PBS is 6:1:3; the core-shell structure is a PGA / PBS core-shell structure with PGA as the core and PBS as the shell dispersed in the PLA matrix; The method for preparing the degradable three-phase polymer mixed membrane with a core-shell structure comprises the following steps: S1. PGA, PBS and epoxy compatibilizer are mixed, melt extruded and granulated to obtain a binary mixed material masterbatch; S2. PLA, epoxy compatibilizer and the binary mixed material masterbatch are mixed, and melt extruded and granulated to obtain a ternary mixed material masterbatch; S3. Casting the ternary mixed material masterbatch to obtain a degradable three-phase polymer mixed film; The epoxy compatibilizer is epoxy soybean oil branched cardanol ether.
2. The use of the degradable three-phase polymer mixed film with a core-shell structure in food preservation according to claim 1, characterized in that: The preparation method of the epoxy soybean oil branched cardanol ether is as follows: ESO and CD are mixed and then subjected to a catalytic reaction; the product obtained by the catalytic reaction is mixed with concentrated sulfuric acid and heated; a mixture of glacial acetic acid and hydrogen peroxide is added dropwise for stirring reaction; after the reaction is completed, extraction and separation are performed, and the solvent is removed to obtain the epoxy soybean oil branched cardanol ether.
3. The use of the degradable three-phase polymer mixed film with a core-shell structure in food preservation according to claim 1, characterized in that: The epoxy compatibilizer added in S1 is 0.5 phr of the total mass of PGA and PBS.
4. The use of the degradable three-phase polymer mixed film with a core-shell structure in food preservation according to claim 1, characterized in that: The epoxy compatibilizer added in S2 is 0.5 phr of the total mass of PLA and the binary mixed material masterbatch.
5. The use of the degradable three-phase polymer mixed film with a core-shell structure in food preservation according to claim 1, characterized in that: The temperature of the melt extrusion granulation in S1 and S2 is 195-225°C; the temperature of the tape casting in S3 is 180-230°C.
Citation Information
Patent Citations
A bio-based epoxy chain extender, its preparation method and application
CN116693471B
Preparation method of bio-based compatilizer modified PLA / P34HB full bio-based high-barrier film material
CN117924220A